Juridical Review of the Carrier's Responsibility for the Loss of Goods Sent Through Road Transportation Based on Law Number 22 of 2009 Concerning Traffic and Road Transportation - Esraini Saruksuk; Janpatar Simamora; Meli Hertati Gultom (International Journal of Law and Society, 2025)
This study addresses the legal responsibility of carriers for the loss or damage of goods during road transportation, as stipulated in Law Number 22 of 2009 concerning Traffic and Road Transportation (UU LLAJ). Article 193 of UU LLAJ obliges carriers to provide compensation for any loss incurred during transportation, except in cases of force majeure or third-party negligence. The study also explores the application of breach of contract (wanprestasi) and strict liability principles as the legal foundation for carrier accountability. However, the practical implementation of these regulations often faces challenges, including unclear contractual clauses on liability, difficulties in proving carrier negligence, and slow or inefficient dispute resolution mechanisms. To address these issues, the study proposes strategic measures such as regulatory revisions to clarify carrier liability boundaries, the establishment of standardized transportation contracts, enhanced legal education for stakeholders, strengthened non-litigation mechanisms like mediation and the Consumer Dispute Resolution Agency (BPSK), and the optimization of insurance to mitigate risks. These recommendations aim to foster a more efficient, reliable, and legally protective transportation system for all stakeholders involved.